Acceptability of digital vending machines to improve access to sexual and reproductive health in Brighton, UK: a qualitative analysis - Jaime H Vera; Richard Cooper; Syra Dhillon; John Mear; Gillian Louise Dean; Rhys D Wenlock (BMJ Publishing Group, 2024)
Introduction Sexual health remains a public health priority and relies on widely available testing to enable prompt diagnosis and treatment. Technology-based approaches to distribute tests have potential to increase access and enable prompt diagnosis and treatment. We evaluated the acceptability of vending machines (VMs) to distribute HIV self-test (HIVST) and sexually transmitted infection (STI) self-sample kits, from the service user and stakeholder perspective.Methods Six VMs were placed across Brighton and Hove (UK) in publicly accessible locations. After use, individuals received a text with an online questionnaire link. Participants completing the questionnaire were invited to a semistructured interview. Stakeholders were staff on sites where the VM was placed. Data analysis took place on NVivo, using a thematic approach.Results 12 users completed the interview. 42% within the age 18-25 years with equal male and female identifying distributions. 33% were heterosexual, 25% homosexual and 33% bisexual. VM acceptability was high with anonymity and instant access as main benefits. Some participants expressed concern that the public location of the VM may deter others from using it. Participants found the HIVST mouth swabs were acceptable, although there was concern over accuracy. Participants welcomed being able to access comprehensive sexual health screening through a VM. Five stakeholders completed the interview. There was recognition that a publicly visible VM led to positive sexual health conversations between service users and staff. There were initial issues with restocking and machine hardwiring.Conclusions VMs to distribute HIV and STI testing kits is acceptable to service users and stakeholders. The main reported benefits are increased confidentiality, privacy and immediate access. Further education referencing the accuracy of the HIVST mouth swab may alleviate concerns. From a stakeholder perspective, the pathway is beneficial and the role of community champions to reduce stigma is favourable.